Destete precoz de becerras bajo condiciones desfavorables: crecimiento, consumo de alimento y eficiencia de conversión alimenticia - Butterworth, M.H. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Means, ranges and standard deviations were calculated for growth and food consumption parameters for 99 Holstein heifer calves from birth to 12 weeks of age. The following parameters were used: Body weight, thoracic perimeter, height at the wither's, body length, circumference of cannon bone, food consumption and efficiency of food conversion. The calves had been reared using an early weaning system in Monterrey, N.L., Mexico where the climate may be classified as extremely hot and semi-arid. The results obtained were compared with those of other studies carried out both in tropical and sub-tropical regions as well as in temperate climates. With the exception of height at the withers and cannon bone circumference, the data were in general lower than those reported for temperate climates but similar to those from tropical and sub-tropical climates. It was shown that birth-weight did not influence weight gain until up to three months, nevertheless, weight gain up to the 4th week of age influenced future gains. Total food consumption was correlated with weight gain up to 12 weeks of age. Food consumption during the fifth week was highly correlated with total food consumption.